NUTRITIONAL STATUS, DETERMINANTS, AND CONSUMPTION OF IRON AND FOLATE-RICH FOODS AMONG FEMALE ADOLESCENTS IN SELECTED SCHOOLS OF ZARIA LGA, KADUNA STATE (FUDMA JOURNAL OF SCIENCES, 2025)
Adolescent girls face challenges in meeting their nutritional needs due to biological, cultural, and economic factors, including inadequate intake, and also face a wide range of nutritional disparities across different socio-economic statuses. The current study assesses the nutritional status, determinants, and consumption patterns of micronutrient-rich food among female adolescents in selected schools. Exactly 318 healthy adolescent girls were recruited as the study participants. A validated semi-structured questionnaire (SSQ) was used to collect data on socio-economic and demographic characteristics, and determinants, while a food frequency questionnaire (FFQ) was used for food consumption patterns. Body Mass Index for-age z-score (BAZ) was used to evaluate the nutritional status of the adolescent girls. The result of the study found most private school adolescent girls to belong to small (36%), nuclear (62%), and monogamous (64%) families with higher weekly food expenditure (69%) compared to their public school’s counterparts. The findings also suggest private school girls have more consistent access to heme sources of iron such as meat (36%), poultry (28%), and seafood (28%), than public school girls. Similar trends were also observed in the adolescent girls' consumption of legumes, fruits, and vegetables, which are good sources of iron and folate. Adolescent girls from public schools reported lower awareness, consumption, and access to iron- and folate-rich foods, with higher percentage (65.41%) being underweight compared to girls from private schools. Finally, private school girls consume higher iron and folate-rich diets, indicating socioeconomic factors impacting access and quality, resulting in higher undernourishment rates among public school girls.
Keywords: Nutritional status; Iron; Folate; Consumption; Adolescent girls